A Cross Sectional Analysis of Frailty and Markers of Frailty in Young People Living with HIV/AIDS - Nair D R; Sashindran V K; Aggarwal V (Journal of Public Health International, 2024)
Background Frailty is an ageing-associated state linked to poor prognostic outcomes. Chronic inflammation due to HIV-infection, AIDS-related infections. and the adverse effects of antiretroviral therapy (ART) all contribute to frailty in people living with HIV/AIDS (PLHA). Frailty has been comprehensively studied in populations comprising predominantly of Caucasian PLHA. However, there remains a dearth of such data in Indian populations, especially in younger PLHA. Methodology This cross-sectional study aimed to estimate the prevalence of frailty in PLHA (18 - 50 years) who had been on ART for 24-60 months and identify markers linked to frailty. Frailty was assessed in 152 subjects using the Fried frailty-index. Parameters measured included the mid-upper arm and calf circumferences, pain-severity (using the Brief Pain Inventory), highly-sensitivity C-reactive protein, d-dimer, and interleukin-6. Results The prevalence of frailty and pre-frailty were 6.58% and 23.02%, respectively. Reduced grip strength and self-reported exhaustion were associated with frailty (15.79% and 13.16%, respectively). Low calf-circumference and mid-upper arm circumference were not significantly associated with frailty/pre-frailty. The prevalence of pain was 21.7% and both pain severity and pain interference were significantly associated with frailty/pre-frailty. CD-4 counts at the time of assessment showed an inverse association with frailty. Elevated C-reactive protein (CRP of 0.04 associated with 0.49 probability of frailty (95% CI 0.40 – 0.59), CRP of 0.12 associated with 0.63 probability of frailty (95% CI 0.47 – 0.76)). D-dimer levels were not significantly associated with frailty /pre-frailty. Conclusion In this first-of-its-kind study on frailty in young PLHA (mean age 37 years) from the Indian sub-continent, the prevalence of frailty and pre-frailty was 6.58% and 23.02%, respectively. Multivariate analysis showed a strong association of frailty with pain severity, CD4 count at time of assessment, hs-CRP levels and duration of ART.
Keywords: Chronic inflammation